PEMBAGIAN HARTA WARISAN DALAM MASYARAKAT MINANGKABAU DI KECAMATAN MEDAN AREA KELURAHAN TEGAL SARI III KOTA MEDAN - IRLIA ROZALIN (PREMISE LAW JURNAL, 2016)
The change in the inheritance law of Minangkabau was identified by the agreement among ninik mamak (clan heads), cerdik pandai (the intellectuals), and generasi muda (the youth) in Bukittinggi in 1952. The agreement was strengthened by the seminar on the Minangkabau Customary Law in Padang in 1968. One of the clause was that joint property inherited by heirs had to comply with Faraid (religious obligation). The out-migrated Minangkabau community creates acculturation which influences their way of perception and thinking. Based on this background, the researcher studied the distribution of inheritance among the out-migrated Minangkabau community The Distribution of inheritance in the Minangkabau community at Kelurahan Tegal Sari III, Medan Area Subdistrict, Medan, is based on the Islamic Law. The factors of compliance and piety will cause customary law to be avoided. The change in heritance law can also accurs because of the factors of necessities of life. Keywords : Distribution of Inheritance, JointProperty,Minangkabau